Optimization of lipase production by Bacillus Subtilis 20B (Bangladesh Journal of Botany, 2025)
This study aims to screen out the potential lipase-producing bacteria and optimize different culture parameters to produce maximum lipase enzyme. A total of twenty-nine lipase-positive bacteria were isolated from organic waste. Among them, Bacillus subtilis 20B was found to be a potential candidate. The optimum pH and temperature of lipase production by the isolate were 7º and 37ºC, respectively, and the lipase production was 11.72 ± 0.25 U/ml. When the isolate was cultured in medium supplemented with starch as a carbon source, the isolate produced a better level (28.39 ± 1.19 U/ml) of lipase. On the other hand, lipase production increased up to 21.61 ± 0.75 U/ml when yeast extract was used as a nitrogen source. After optimization of inoculum concentration, enhanced lipase production was 51.17 ± 0.50 U/ml. Through optimization, lipase production increased up to 84.30 ± 0.17 U/ml, which was 7.19-fold higher than before. The present study provides useful information about lipase production by indigenous B. subtilis 20B, which may be used as a potential bacterial source of lipase for further study involving lipid-rich wastewater treatment and other purposes.Bangladesh J. Bot. 54(1): 129-136, 2025 (March)